Ketumpatan arus genting antara butiran superkonduktor Bi1.6Pb0.4Sr2Ca2Cu3O10 dalam bentuk pukal dan pita bersarung perak dengan penambahan nanozahrah magnet NiF2, CoFe2O4 dan Co0.5Ni0.5Fe2O4 sebagai pusat pengepinan fluks - Muhammad Hafiz, Mazwir (2015)
The effects of nanometer sized particles NiF2, CoFe2O4 and Co0.5Ni0.5Fe2O4 addition on the superconducting properties of (Bi1.6Pb0.4)Sr2Ca2Cu3O10 in bulk and tape form were investigated. (Bi1.6Pb0.4)Sr2Ca2Cu3O10 superconductor powder was prepared using co-precipitation technique. NiF2, CoFe2O4 dan Co0.5Ni0.5Fe2O4 nanoparticles with average sizes of 10 nm, 60 nm and 20 nm respectively were added to the (Bi1.6Pb0.4)Sr2Ca2Cu3O10 superconductor with nominal composition 0.00, 0.01, 0.02, 0.03, 0.04 and 0.05 wt.%. Effect of the nanoparticles addition on the phase formation, microstructure, critical temperature and critical current density, Jc in zero and applied magnetic field was investigated. X-ray diffraction (XRD) results showed that samples with Co0.5Ni0.5Fe2O4 nanoparticle addition have the highest Bi-2223 phase volume fraction compared to other samples. Samples with NiF2 nanoparticle addition showed a lower Bi-2223 phase volume fraction compared to the non-added samples. The zero- critical temperature, Tc-zero for non-added sample was 97 K. The sample with 0.01 wt.% Co0.5Ni0.5Fe2O4 addition showed the highest Tc-zero of 102 K, which is higher than the critical temperature for non-added sample. The highest Tc-zero for samples with NiF2 and CoFe2O4 additions were 96 K (0.04 wt.%) and 99 K (0.01 wt.%), respectively. Samples with nanoparticles addition in other quantities showed a lower Tc-zero value. Critical current density in self-field for all samples with nanoparticle addition was higher than non-added samples. Samples with the maximum Jc were chosen to be fabricated into Ag-sheathed tapes which were 0.04 wt.% NiF2, 0.01 wt.% CoFe2O4 and 0.01 wt.% Co0.5Ni0.5Fe2O4 added samples. The tapes were prepared using the powder-in-tube (PIT) method and divided into two groups sintered at 845 °C for 50 and 100 h. XRD analysis showed Bi-2223 as the dominant phase in all tape samples, with Bi-2212 as the secondary phase. All tapes showed two to three times higher value of Jc in zero-field compared with non-added tapes. This shows that the addition of nanoparticles increased the critical current density of (Bi1.6Pb0.4)Sr2Ca2Cu3O10 superconductor. Tapes that were sintered for 100 h also showed a higher value of Jc compared to tapes that were sintered for only 50 h. At 30 K, Jc for tapes with NiF2, CoFe2O4 and Co0.5Ni0.5Fe2O4 addition sintered for 100 h were 17270 A/cm2, 22420 A/cm2 and 19830 A/cm2, respectively. Jc of non-added tape at temperature of 30 K was 8280 A/cm2. Jc decreased with increasing temperature due to thermal flux creep. Jc in applied magnetic field of tapes with nanoparticle is also higher compared with non-added tapes. Jc decreased when the applied magnetic field was increased. Flux activation energy in bulk samples was calculated and it showed correlation with value of Jc. This work showed that the presence of small amount of NiF2, CoFe2O4 and Co0.5Ni0.5Fe2O4 nanoparticles can increase the critical current density of (Bi1.6Pb0.4)Sr2Ca2Cu3O10 superconductor.